Optimization of Date Palm Extract (Phoenix dactylifera L.) Based Collagen Powder Beverage Formula with Spices (Tamarind and Cinnamon) Addition Using D-Optimal Mixture Design Method - Raihanurrabb Pawestriaji; Tri Dewanti Widyaningsih (Biology, Medicine, & Natural Product Chemistry, 2025)
The trend of collagen-based beauty functional drinks is predicted to increase. However, its use can potentially cause a fishy taste, so it is usually formulated together with fruit or spice extracts. Date fruit has the potential for high bioactive content, but its utilization as a powder drink in Indonesia is still relatively low. Tamarind and cinnamon are also Indonesian spice commodities that are rich in bioactive components and have a strong flavor that can cover the fishy taste of collagen. Thus, this study aimed to obtain the optimal formulation and the effect of the addition of date, tamarind, cinnamon, and hydrolase collagen powder on the physicochemical characteristics of the final product using the Design Expert program D-Optimal Mixture Design Method. The first stage of the research was determining the upper and lower limits of the independent variables and a fixed value. The optimal formula suggested by Design Expert consisted of 50% date powder, 24,91% tamarind powder, 20,09% cinnamon powder, and 5% hydrolase collagen powder with a desirability value of 0,805. The second stage of characterization testing in the form of chemical tests resulted in antioxidant activity (IC50) of 263,25 ± 8,01 ppm and total phenol content of 101,71 ± 9,21 mg GAE / 100 g. Characterization in the form of physical tests resulted in a moisture content of 2,98 Â± 0,01%, dissolving time of 20,52 ± 0,72 seconds, bulk density of 0,52 ± 0,14 g/ml, and hygroscopicity of 18,73 ± 0,04%.